2022
DOI: 10.24114/jpkim.v14i1.32112
|View full text |Cite
|
Sign up to set email alerts
|

Development of chemic media (chemistry comic) based on problem based learning on chemical bond materials for class x students

Abstract: This research is a development research that aims to determine the feasibility of chemic media based on problem based learning on chemical bonding material for class X students based on BSNP standards. In this research, a modified ADDIE development model was used where only the analysis, design, development and evaluation stages were carried out. This research will be conducted at the Department of Chemistry State University of Medan, SMAN 1 Secanggang and SMAS Bintang Langkat. The feasibility of the media is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This research is in line with Ayu (2019) and Santika (2019), which state that i-Spring media can help students understand the material. Furthermore, research conducted by Purba et al (2020) states that project-based learning models effectively improve skills and knowledge (Nisa et al 2022;Siahaan et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This research is in line with Ayu (2019) and Santika (2019), which state that i-Spring media can help students understand the material. Furthermore, research conducted by Purba et al (2020) states that project-based learning models effectively improve skills and knowledge (Nisa et al 2022;Siahaan et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This means that students play an active role in learning activities and the teacher only acts as a facilitator and mediator. The 2013 curriculum learning activities include several activities, namely observing, asking questions, gathering information, associating, and communicating (Nisa et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research conducted by Nisa et al (2021) regarding the development of comicbased learning media on the reaction rate, it showed that student learning outcomes met the KKM and some even exceeded the KKM. The researcher concluded that students were very enthusiastic about using chemistry comic books in understanding reaction rates (Sari & Harahap, 2021;Nisa et al 2022) and of course increasing student motivation and learning outcomes.…”
Section: Introductionmentioning
confidence: 99%